Exploring the Depths of Human Curiosity (CIPEEX, 2025)
The objective of this monograph was to investigate the concept of an Unconstitutional State of Affairs (ECI) in the context of the Brazilian prison system, analyzing the application of this concept by the Federal Supreme Court (STF) in the judgment of Argument for Non-compliance with a Fundamental Precept (ADPF) No. 347. The study examined the origins of this concept in the Colombian Constitutional Court and its adaptation to Brazil, highlighting the structural flaws that have generated serious violations of prisoners’ human rights. The methodology included a bibliographical review, analysis of relevant doctrines and research and a case study of the ADPF No. 347, as well as empirical research in the Itapuranga-GO prison unit, using a questionnaire sent to the director. As a result, the work pointed to deficiencies in the prison system in Itapuranga, confirming the presence of elements characteristic of the ECI. It was concluded that the effectuation of prisoners’ fundamental rights required structural interventions and the adoption of the proposed judicial measures, illustrating the importance of judicial activism and mechanisms of constitutionality control for the promotion of justice and human dignity in the prison system. Keywords: ADPF 347. Affairs. State. Unconstitutional. Traduzido por Adair José Justino Cassimiro Professor Licenciado em Letras Português/Inglês pela Universidade Estadual de Goiás (UEG).
Keywords: ADPF 347; Affairs; State; Unconstitutional